A Survey on Data Acquisition Systems DAQ - Abdallah, M.; Elkeelany, O. (International Conference of Computing in Engineering, Science and Information, 2009)
Data acquisition systems have been used in various applications in our world. Numerous techniques and algorithms have been employed to achieve high quality acquisition. Each application has its own philosophy and data acquisition structure. Hence, in this paper, a survey on data acquisition systems has been presented. Different DAQ categories have been introduced. A comparison study between these categories has been presented. Different applications that need DAQs have been mentioned in more details illustrating DAQ technique used for each application.